Actor Network Model of the Construction Mechanism of a Technology Standardization Innovation Ecosystem—Haier Case Study - Yu Yuan; Dengyun Ma (Systems)
As the competition of standards among enterprises turns to the competition among innovation ecosystems, how to construct the technology standardization innovation ecosystem (TSIE) is of great significance to enhance the competitiveness of enterprises and even industries. Based on the perspective of actor network theory (ANT) through the case study of Haier, this paper constructs an ANT model for the formation of a TSIE and tries to answer the following questions: how is the TSIE formed? how do the actors gather and what roles do they play in the formation process? and what role do technology standards play in the formation process? This research finds that the formation of the TSIE results from interactions among the actors of ANT over different periods. The focal actors play a crucial role; their roles change from the construction of their own actor network to the empowerment of the sub-actor network construction. Other actors evolve from being defined to defining roles themselves. Standards are also crucial throughout this process: initially, they recruit and coordinate the primary actors to form close relationships, and later they facilitate bidirectional regulation, enable standardization, and coordinate the formation and development of sub-ecosystems. This paper explores the evolution of TSIE through the lens of ANT, advancing its application within this context. It enriches the theoretical research on this subject and offers a theoretical foundation for large enterprise platforms to facilitate the transformation of TSIE.